Decision-Making by Individuals in Conflict of Interest: A Case Study of a Civil Servant who Doubles as the Owner of a Private Sectors in Yogyakarta - Atmojo, Danang Puji; Aoki, Haruka (Vox Populi, 2024)
This study aims to analyze the conflict of interest experienced by individual employees of government agencies in the Special Region of Yogyakarta who are active in private art institutions. The theoretical framework used in the research includes the concept of conflict of interest and decision-making theory. The research method used is an interpretative phenomenological approach that focuses on describing and interpreting the direct subjective experiences of individuals related to the phenomenon of conflict of interest. Data were obtained through direct interviews with the interviewees, who are former civil servants in a Yogyakarta government agency and owners of private cultural studios. The results show that the Special Fund allocated has had a significant impact on the development of arts and culture in Yogyakarta, but has also resulted in conflict of interest issues among individuals who play multiple roles. The conclusions of the study highlight the importance of clear legal regulations related to conflict of interest as well as the need for a deeper understanding of ethics and public duty for individuals who play a role in both sectors.